2021
DOI: 10.1212/wnl.0000000000011852
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity and APOE Genotype With Longitudinal Cognitive Change in Early Parkinson Disease

Abstract: Objective:To determine whether greater physical activity could modify the negative association of APOE ε4 with longitudinal cognitive changes in early Parkinson’s disease (PD) and to uncover the disease-specific mechanism for explaining such benefits of physical activity.Methods:We used data from the Parkinson’s Progression Markers Initiative cohort. Because self-reported physical activity, measured by the Physical Activity Scale of the Elderly, was initiated at 2 years after enrollment, this longitudinal anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Previous observational studies have preferentially focused on the effect of baseline physical activity levels and have shown that high baseline exercise habits and regular overall physical activity levels are associated with better clinical course of PD over a few years. 13 - 17 Therefore, we were initially surprised by our observation that not their baseline level but the maintenance of their level is the key factor associated with better clinical course of PD over a longer period of time. However, given the gradual decline in physical activity levels in patients with PD ( Figure 1A ) and the reported gradual decline in the effectiveness of interventional exercise, 43 , 44 it seems quite plausible that the focus should be on a sustained increase in exercise and regular physical activity levels to improve long-term clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous observational studies have preferentially focused on the effect of baseline physical activity levels and have shown that high baseline exercise habits and regular overall physical activity levels are associated with better clinical course of PD over a few years. 13 - 17 Therefore, we were initially surprised by our observation that not their baseline level but the maintenance of their level is the key factor associated with better clinical course of PD over a longer period of time. However, given the gradual decline in physical activity levels in patients with PD ( Figure 1A ) and the reported gradual decline in the effectiveness of interventional exercise, 43 , 44 it seems quite plausible that the focus should be on a sustained increase in exercise and regular physical activity levels to improve long-term clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…It remains possible that we have overlooked some of effects of regular physical activity if it has different effects on different genotypes, as suggested by a recent important observational study showing the interaction effects among regular physical activity, APOE genotype, and global cognitive function. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Inspired by these observations, we aimed at assessing whether low lymphocyte count is associated with the subsequent development of the key milestones in PD's disease course, specifically cognitive impairment, with a particular attention to the apolipoprotein E (ApoE) ε4 allele, a crucial modifying factor in cognitive impairment. 5 , 6 …”
mentioning
confidence: 99%
“…11,12,13,14,15 Extracellular-vesicle-associated tau and amyloid β42 have also been reported to correlate with cognition in PD. 16 Additionally, genetic variants have been linked to cognitive trajectory in PD, 17,18,19 with the most well-replicated effects on cognition seen for the APOE E4 allele 20,21,22,23 and PD-associated GBA variants. 17,24,25,26 Studies to date, however, have limitations that hamper translation of biomarkers of PD cognitive decline into clinical contexts.…”
Section: Introductionmentioning
confidence: 99%